Vasculogenesis of decidua side population cells of first-trimester pregnancy - Wang, Qiushi (BioMed Central, 2013)
INTRODUCTION: Sufficient uterine blood supply is essential for the fetus to develop normally in the uterus. Several mechanisms are involved in the process of vessel development in deciduas and villus. We focus on whether first-trimester decidua side population (SP) cells contain cells capable of differentiating into endothelial cells. METHODS: Eight decidua samples were collected from healthy women, 22- to 30-years old, undergoing elective terminations of early pregnancy (six to eight gestational weeks). The cell suspensions from human deciduas were stained by Hoechst 33342 and sorted by flow cytometry, further cultured under differentiation conditions and analyzed for specific markers. These cells were implanted into ischemic limbs of nude mice to test the capacity of angiogenesis in vivo by DiI tracers and immunohistochemistry. RESULTS: Decidua CD31(-)CD146(-) SP cells of first-trimester human pregnancy can differentiate into endothelial cells, express the corresponding specific markers of endothelial cells, such as CD31 and CD146, and form tube-like structures on Matrigel and part of newly formed vessels in the ischemic limbs of nude mice. Vascular endothelial growth factor was more effective in promoting proliferation of CD31(-)CD146(-)SP cells compared with other growth factors, and estrogen and progesterone at a final concentration of 10 μmol/L and 30 μmol/L, respectively, promoted the migration of CD31(-)CD146(-)SP cells in a dose-dependent manner. CONCLUSIONS: CD31(-)CD146(-) SP cells may be involved in the formation of new vessels in the maternal aspect of the placenta in the first trimester.